Variations in hospitalisation costs for acute myocardial infarction - a comparison across Europe - Tiemann, Oliver (Health economics, 2008)
The aim of this study was to determine whether between‐country variations in hospital costs are larger than within‐country variations and, furthermore, to explore reasons for this variability. For this purpose, we chose the primary treatment of patients with acute myocardial infarction (AMI) as an episode of care. We obtained hospitalisation costs and reimbursement rates from 45 hospitals in nine different EU member states (i.e. Denmark, England, France, Germany, Hungary, Italy, Netherlands, Poland, and Spain) for the year 2005. To further analyse the variations in hospital costs, we employed a hierarchical random effects model based on treatment and hospital characteristics and using purchasing power parities (PPPs) as a proxy for country‐specific price levels. The between‐country standard error was estimated at €2473, whereas the within‐country standard error was estimated at €1242. Our regression analysis showed that percutaneous coronary intervention was associated with significantly increased hospitals costs compared to other treatment strategies. We were able to distinguish between three groups of countries with different cost levels based on the number of hospitals that were able to provide these services (i.e. percutaneous transluminal coronary angioplasty (PTCA) with intracoronary stenting). Excluding Hungary, Poland, and Spain, where none of the participating hospitals were able to provide these procedures, the between‐country standard error decreased to €1632, whereas the within‐country standard error increased to €1416. Finally, we observed exogenous price‐level effects between countries and within countries for hospitals located in urban areas. Copyright © 2008 John Wiley & Sons, Ltd.